Financial frauds and pseudo-states in the Pacific Islands - Van Fossen, Anthony B. (Crime, law and social change, 2002)
Since 1990 financial frauds have been associated with pseudo-states in the Pacific Islands, particularly the Dominion of Melchizedek. The relative success of these schemes can be understood in terms of (i) the general atmosphere of overconfidence about financial dealings that prevailed during the decade to early 2000, (ii) Melchizedek's creation of opportunities for a growing mutually supportive network of fraudsters, (iii) this pseudo-state's identification with a rising global tide of secession and indigenous self-determination through its increasing involvement in a variety ofethnic nationalist movements in Oceania that have been connected with questionable financial dealings, and (iv) the attractiveness of its developing postmodern personality as a libertarian cyber-state. The article concludes by seeing Melchizedek's facilitation of financial frauds as a challenge to recent libertarian thinking about the law of cyberspace and the anticipated neo-medieval world-system.